2004
DOI: 10.1093/hcr/30.1.8
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Deceit Via Analyses of Verbal and Nonverbal Behavior in Children and Adults

Abstract: This experiment examined children's and undergraduates' verbal and nonverbal deceptive behavior, and the extent to which their truths and lies could be correctly classified by paying attention to these responses. Participants (N = 196) aged 5-6, 10-11, and 14-15, as well as university undergraduates, participated in an erasing the blackboard event, and told the truth or lied about the event afterwards. Nonverbal and verbal responses were coded, the latter with Criteria-Based Content Analysis and Reality Moni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
147
2
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(163 citation statements)
references
References 49 publications
12
147
2
2
Order By: Relevance
“…More importantly for our purposes here, speech latency measures also are sensitive to deception. Vrij, Edward, Roberts, and Bull (2000) showed that response latencies (measured by voice onset times) are longer in deceptive than true statements (see also Spence et al, 2012;Sporer & Schwandt, 2006). Regarding language context, foreign language production elicits longer naming latencies and utterance durations than the native one does (BlumKulka & Olshtain, 1986;Ivanova & Costa, 2008;Sadat, Martin, Alario, & Costa, 2012;Strijkers et al 2013 for a review).…”
Section: Introductionmentioning
confidence: 99%
“…More importantly for our purposes here, speech latency measures also are sensitive to deception. Vrij, Edward, Roberts, and Bull (2000) showed that response latencies (measured by voice onset times) are longer in deceptive than true statements (see also Spence et al, 2012;Sporer & Schwandt, 2006). Regarding language context, foreign language production elicits longer naming latencies and utterance durations than the native one does (BlumKulka & Olshtain, 1986;Ivanova & Costa, 2008;Sadat, Martin, Alario, & Costa, 2012;Strijkers et al 2013 for a review).…”
Section: Introductionmentioning
confidence: 99%
“…Sporer and Schwandt (2007) outline several reliable indicators of deception, such as nodding, movement of feet and legs and hand movements; however, they showed no systematic relationship between avoidance of eye contact and deception. However, researchers and professional practitioners in the field have suggested that clusters of behaviours are better indicators of changes in emotion and possible psychological discomfort, which may arise from attempting to deceive someone (DePaulo et al 2003;Navarro andKarlins 2008, Navarro 2011;Vrij et al 2004). The present research continues a more recent trend in NVC by investigating the possibility that it is not only discrete behaviours or clusters of movements that can be used to indicate emotion or distress but also the sequence that these movements occur in (Burgoon et al 2014;Burgoon et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to looking at single behaviours or micro reactions, researchers have suggested that 'clusters' of behaviours are better indicators of changes in emotion and psychological distress, which may reflect attempts to deceive (DePaulo et al 2003;Hartwig and Bond 2011;Navarro and Karlins 2008;Vrij et al 2004). Therefore, simply recognising one single behaviour as an indication of emotions or lying is not completely reliable, though Hartwig and Bond (2011) highlight that while multiple cues may be better than single cues, individual behaviours still contribute a lot to the detection of deception.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has suggested that liars gesture differently than truth tellers do [11][12][13]. A common perception among those who try to identify deception is that an increased number of adaptor gestures such as fidgeting and foot tapping are indicators of deception.…”
Section: Current Researchmentioning
confidence: 99%
“…However a decrease in the number of illustrator gestures has been linked with deception [11][12][13] Increased cognitive load has been suggested as a possible reason for the decrease in illustrator gestures. The deceiver may be more concerned with fabricating a realistic lie than with punctuating that lie with hand gestures.…”
Section: Current Researchmentioning
confidence: 99%